A reduced role for water transport during the Cenozoic evolution of epiphytic Eupolypod ferns. Issue 5 (5th January 2023) - Pittermann, Jarmila; Baer, Alex; Campany, Courtney; Jansen, Steven; Holmlund, Helen; Schuettpelz, Eric; Mehltreter, Klaus; Watkins, James E.
Summary: The Cretaceous–Cenozoic expansion of tropical forests created canopy space that was subsequently occupied by diverse epiphytic communities including Eupolypod ferns. Eupolypods proliferated in this more stressful niche, where lower competition enabled the adaptive radiation of thousands of species. Here, we examine whether xylem traits helped shape the Cenozoic radiation of Eupolypod ferns. We characterized the petiole xylem anatomy of 39 species belonging to the Eupolypod I and Eupolypod II clades occupying the epiphytic, hemiepiphytic, and terrestrial niche, and we assessed vulnerability to embolism in a subset of species. The transition to the canopy was associated with reduced xylem content and smaller tracheid diameters, but no differences were found in species vulnerability to embolism and pit membrane thickness. Phylogenetic analyses support selection for traits associated with reduced water transport in Eupolypod 1 species. We posit that in Eupolypod epiphytes, selection favored water retention via thicker leaves and lower stomatal density over higher rates of water transport. Consequently, lower leaf water loss was coupled with smaller quantities of xylem and narrower tracheid diameters. Traits associated with water conservation were evident in terrestrial Eupolypod 1 ferns and may have predisposed this clade toward radiation in the canopy.